Epidemiologia molecular de rotavírus em rebanhos bovinos no estado de São Paulo no período de 2006 a 2010 - Siqueira, Heloisa Pinto de Godoy [UNESP] (2015)
Rotavirus is the major causative agent of diarrhea in several animal species and humans, causing large economic and public health damage. A striking feature of this virus is the great genotypic diversity of circulating strains. Genotyping information is essential to establish surveillance mechanisms of rotavirus infection. This study aimed to discuss the epidemiology of rotavirus in cattle through studies conducted between 2006 and 2010, the Rotavirus Disease Laboratory of the Faculty of Agriculture and Veterinary Sciences of the Universidade Estadual Paulista Julio de Mesquita Filho (FCAV / UNESP), 803 samples of feces of calves were obtained, ranging in age from 1 to 90 days, with and without diarrhea, 48 herds of dairy and beef cattle in the State of São Paulo. The samples were characterized on the basis of electrophoresis tests on polyacrylamide gel (PAGE) and then reverse transcription polymerase chain reaction (RT-PCR). The PAGE test indicated positive animals in 33.3% (16/48) of the herds and 6.1% (49/803) of the samples. In dairy herds infected animals were detected rotavirus in different age groups (P> 0.05), while in the high frequency cut herds (22.8%) of positive samples was observed in calves between 1 to 15 days (P <0,05). The genome profile analysis in PAGE identified seven eletropherotypes characteristic of rotavirus group A, indicating a high genomic diversity of rotavirus in the herds. The molecular characterization of genotype G (VP7) and P (VP4) by RT-PCR identified the genotype G6P [5] as the most common. Maps were constructed to analyze the spatial distribution of detected rotavirus. Rotavirus identification work is of great value, since it is evident that different genotypes agent is spread in São Paulo presenting different forms of production